THE INFLUENCE OF MIND MAPPING TECHNIQUE AND LEARNING MOTIVATION TOWARD THE TENTH GRADE STUDENTS DESCRIPTIVE TEXT WRITING ABILITY AT SENIOR HIGH SCHOOL 1 OF BAYUNG LENCIR - Rusman Roni; Mulyadi Mulyadi; Jeri Apriadi (ELTE Journal (English Languange Teaching and Education), 2017)
This research is conducted in experimental group with the total sample of 30 students of eleventh grade students of SMAN 1 Bayung Lencir in the second semester in the academic year 2016-2017 and it inquiry of the influence of Mind Mapping and Learning Motivation toward Writing Ability. The problem of this study is to find out the significance average score and motivation between Mind Mapping and Conventional Technique. Due the interpretation of this  study, it found that: (1) there was a significant difference in writing achievement between the student who taught by using Mind Mapping and those are taught using conventional technique since it was  found  that the result was 0,29 it was lower than significant level (0,05), (2) there was significant difference in writing achievement between the students who have high motivation by using Mind Mapping teaching and conventional technique since the result was 0,01 and it means that lower than significant level (0,05), (3) there was significant difference in writing achievement between the students who have low motivation by using Mind Mapping and conventional technique since the result was 0,04 and it was lower than significant level (0,05), (4) there was significant difference in writing achievement between the students who have low and high motivation by using Mind Mapping since the significant was lower (0,00) than significant level  (0,05), and (5) there was no an interaction effect of technique used and student’s motivation in improving writing ability since the result of interaction effect was lower (0,36) than the significant level (0,055). Based on the result,  the writer conclude that Mind Mapping and motivation no gave the significant influence for student’s  narrative writing Ability since there was a significant improvement before and after taught Mind Mapping technique. Keywords: Influence, Mind Mapping , Students motivation, Writing.